Optimum connection modes for photovoltaic thermal collectors in different radiation zones of China. (25th July 2017) - Ouyang, Liping; Sun, Liangliang; Yuan, Yanping; Cao, Xiaoling; Xiang, Bo
Highlights: A dynamic heat transfer model for a PVT system of varied connections was developed. The relative errors between simulated and experimental results were within ±5%. The proposed model was applied to 10 cities in radiation zone II and III of China. The optimum connections were 2 and 3 in radiation zone II and III, respectively. Abstract: The connection mode of photovoltaic thermal (PVT) collectors is critical factor influencing the performance of PVT system. While determining optimum connection modes for PVT collectors in different radiation zones has not been previously reported in published literatures. In this study, a dynamic heat transfer model representing different connection modes for a PVT hot water system was developed, validated, and applied. By considering the ambient temperature, solar radiation, and heating load concurrently, the optimum connection mode in 10 different cities was determined based on an optimization index of realized combined electrical energy. The results indicated that the connection modes corresponding to the maximum realized combined electrical energy were N  = 2 and N  = 3 in radiation zone II and III, respectively, where N is the number of collectors in series. In Shantou, high ambient and main water temperatures contributed to a 40 MJ increase in the realized combined electrical energy when the connection mode changed from N  = 3 to N  = 2. The results of this study provide good guidance for determining optimum connection modes for PVT hot water systems in different radiation zones.